ANALISIS PENERAPAN PSAK NO. 45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA (NON PROFIT) TERHADAP PENYAJIAN LAPORAN KEUANGAN PADA YAYASAN OIKUMENE KALIMANTAN BARAT - B51111127, RATNA PERTIWI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Most of nonprofit organization in Indonesia, stressed more on the goals of work programs rather than the systems of financial management report. Though, financial management report believed to be one of priority measurement towards organization's accountability and transparency. Just me sermons is stated in "Pernyataan Standar Akuntansi Keuangan" (PSAK) number 45 about financial reporting of nonprofit organization. Oikumene Foundation is one of the nonprofit organizations that works especially in cemeteries field. Initial report of this organization has a problem according to PSAK number 45. This is why the writer interested in writing this research. Research is qualitative descriptive with qualitative analysis using PSAK number 45 international management report, and interview.The result of research shows that are coming this financial report is not appropriate according to PSAK number 45. The report is about gain and loss only. Conclusion of the research is Oikumene Foundation in West-Kalimantan should applying PSAK number 45 in reporting the financial management report. The report should have financial position, activities report, cash-flow report and financial report. The process will be explained in discussion. Keywords: nonprofit entity, PSAK No. 45, Financial Statement, Oikumene Foundation in west Kalimantan